The Effect of Price Fairness and Free Shipping on Purchasing Decisions on the TikTok Application (A Study of the Community in West Kota District, Gorontalo City) - Marali, Firda Agustin Vurman; Isa, Ramlan Amir; Ismail, Yulinda L (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine the effect of price fairness and free shipping on purchasing decisions in the TikTok application. This research uses a quantitative approach with an explanatory method. Data were collected through questionnaires distributed to respondents who are TikTok Shop users. The data were analyzed using multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results indicate that partially, price fairness has a positive and significant effect on purchasing decisions. Free shipping also has a positive and significant effect on purchasing decisions, with a greater influence compared to price fairness. Simultaneously, price fairness and free shipping significantly affect purchasing decisions on the TikTok application. The coefficient of determination shows that both variables explain a substantial proportion of the variance in purchasing decisions, while the remaining variance is influenced by other variables outside this study. These findings suggest that fair pricing strategies and free shipping promotions are important factors in increasing consumer purchasing decisions in e-commerce platforms. Therefore, sellers on TikTok Shop are advised to maintain price fairness perceptions and optimize free shipping programs to enhance competitiveness and customer loyalty.